Non-destructive estimation of lichen biomass - Moen, Jon; Danell, Öje; Holt, Roger (Rangifer, 2009)
Ground lichens constitute a vital part of reindeer winter diet, and non-destructive estimation of lichen biomass is therefore crucial for providing objective data for the management of lichen resources. The aim of this study is to compare precisions of different methods of estimating lichen biomass from ground cover and thallus heights of the four most important lichen species: Cladonia arbuscula, C. rangiferina, C. stellaris, and Cetraria islandica. The methods were validated against actual lichen biomass within 50 cm x 50 cm plots. Different methods gave remarkably similar results, except when cover estimation was based on presence/absence data with a strict criterion of 100% lichen cover. Average thallus heights within the plot explained the variation in lichen biomass as well as lichen volume (estimated from cover and average heights). Relationships between biomass and volume or height were also very similar for all four lichen species, and separation into species thus do not seem necessary for practical purposes. Abstract in Swedish / Sammandrag: Icke-destruktiv skattning av lavbiomassa Marklavar utgör en kritisk del av renars vinterföda, och det blir därmed väsentligt att kunna skatta lavbiomassa på ett icke-destruktivt sätt för att kunna förvalta lavresursen. Syftet med denna studie är att jämföra precisionen hos olika metoder för att skatta lavbiomassa baserat på volym- och bålhöjdsmätningar för de fyra viktigaste arterna: Cladonia arbuscula, C. rangiferina, C. stellaris, and Cetraria islandica. Metoderna validerades mot lavbiomassa mätt i 50 cm x 50 cm provytor. Olika metoder gav anmärkningsvärt lika resultat, förutom när täckning skattades med förekomstdata med ett strikt kriterium av 100% lavförekomst. Medelhöjd på lavbålarna i provytan förklarade lika mycket av variationen i lavbiomassa som lavvolym (baserat på täckning och medelhöjd). Förhållandet mellan biomassa och volym eller bålhöjd var också mycket lika mellan arterna vilket medför att det, för praktiska ändamål, inte är nödvändigt att separera arterna vid skattningar av total biomassa.